Notes on the distribution of the genus Andalgalomys (Rodentia, Cricetidae), with the first record for A. pearsoni (Myers, 1978) in Argentina - Teta, Pablo Vicente (2016)
We documented the first record of Andalgalomys pearsoni (Myers 1978) in Argentina, based on one individual caught at Cerro Colorado (Metán department, Saltaprovince, Argentina). This new record enlarges the distribution of this species, to date only known from Bolivia and Paraguay, ca. 530 km SW and fills a gap without records for Andalgalomys of approximately 850 km between Paraguay and NW Argentina. The finding of this mouse, caught more than 50 years ago, highlights the importance that biological collections have in our understanding ofbiological diversity.